FROM TOUCH TO TRUST: THE ROLE OF EMOTIONAL ENGAGEMENT AND BRAND TRUST IN DRIVING IMPULSIVE BUYING OF SCIENTIFIC PRODUCTS DURING TIKTOK LIVE STREAMING - Diah Sulistia; Muhammad Dharma Tuah Putra; Husni Muharram Ritonga (RADJA PUBLIKA, 2025)
Study This aim explore Factors that influence impulsive buying behavior Students on TikTok Live Streaming Commerce products Skintific with use Stimulus–Organism–Response (SOR) framework . In this model , Interactivity is positioned as the main stimulus , while Affective Engagement and Brand Trust play a role as a mediating organism the influence of stimulus on response in the form of behavior purchase impulsive approach​ quantitative used through Structural Equation Modeling (SEM-PLS) method with involving 300 respondents active students of Panca Budi Development University Medan watch TikTok Live Streaming and have experience shop product beauty online . Research results show that interactivity has an effect significant on affective engagement and brand trust, as well as in a way direct and indirect direct trigger impulsive buying behavior . Findings This confirm that combination real-time interaction , engagement emotional , and trust towards the brand playing role important in push decision purchase spontaneously in the Live Streaming Commerce ecosystem . In theoretical , research This enrich literature about behavior digital consumers , while in a way practical give implications for beauty brands For optimizing communication strategies interactive in increase effectiveness marketing via TikTok Live Streaming.